Economical Approach for Home Automation and Security - Singh, Abhshek (Thapar University, Patiala, 2017)
Home automation is primarily done to improve the comfort level of the users. But, its use for improving the safety and the security from intruders can’t be over looked. It has been observed in this paper that home automation can be used as a great tool to improve security scenario. The work focuses on concept of home security by sending user notification on their smartphones in case user is miles away from house and raising various alarms when user is around. Home automation system and technologies considered here includes central controller arduino or raspberry pi , Wi-Fi camera, sensors network and GSM shield. Consumers also may have certain reservations in using smart home systems viz. cost, performance, data security, privacy, ease of use, installation configuration of the system, management and maintenance etc. but, through constant work on each of these smart home technologies can be made more economical, user friendly and secure which will further attract consumers to trust and use these technologies. The research proposed a system for home security which uses a network of sensors to detect intruders, fire and gas leak and notifies user via email remotely, if the user is connected with the internet he/she will get the notification immediately as the sensor detect something and send the data to micro controller.
Keywords: Home Security; Home Automation; IoT